A review of blockchain cyber security - Dubey, Animesh Kumar (ACCENTS transactions on image processing and computer vision, 2023)
The aim of this review paper is to provide a comprehensive understanding of blockchain security. As cyber-attacks continue to increase, there is a growing need for secure technologies, and blockchain technology has emerged as a promising solution. However, this technology also faces its own set of challenges related to attacks and code encryption. The paper delves into these challenges, along with potential solutions for enhancing blockchain security. The review paper discusses various methods and techniques that have been proposed to ensure the security of blockchain technology. It covers topics such as consensus algorithms, encryption methods, and access control mechanisms. It provides detailed results about several methods used in blockchain security. The paper also discusses the potential implications of using blockchain technology for security purposes in different domains, such as finance, healthcare, and supply chain management. By providing a comprehensive understanding of the challenges and potential solutions in blockchain security, this review paper can serve as a useful resource for researchers and practitioners working in the field.